Removal of Ibuprofen and Diclofenac in Batch Nitrifying Reactors: Effect of Natural Zeolite on the Process - Huilinir-Curio, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Ibuprofen (IBP) and diclofenac (DFC) are two of the most commonly used non-steroidal anti-inflammatory drugs (NSAIDs) to treat inflammation and pain. However, they can impact the environment if not treated adequately before discharge into waterways. Biodegradation through the nitrification process is an alternative to reducing the concentration of these micropollutants (MPs) in wastewater. Thus, this work aimed to evaluate the effect of natural zeolite on IBP and DFC removal in a nitrifying batch reactor. Mini-reactors were set up with 90 mL of inoculum and 110 mL of synthetic wastewater with a concentration of 25 mg total ammonia nitrogen TAN/L, at 25 °C and 1 vvm (volume of air/volume liquid∙min) of aeration. Two conditions were tested: high concentrations (IBP = 700 μg/L, DFC = 100 μg/L) and low concentrations (IBP = 30 μg/L, DFC = 20 μg/L). The research used a concentration of 5 g/L of the natural zeolite. Results indicated that the zeolite negatively affected the nitrification rate. At high MPs concentration, the natural zeolite negatively affects the removal of IBP and DFC, where biodegradation and sorption are the mechanisms that eliminate both NSAIDs. Conversely, at low DFC and IBP concentrations, the natural zeolite improves the removal of IBP and DFC, wherein biodegradation is the primary removal mechanism. © 2023 by the authors.